Answer :

Given tan(A +B) = x And tan(A –B) = y

Consider tan 2A = tan(A +A)

= tan(A +B +A –B)

We know that

Consider tan 2B = tan(B +B)

= tan(B +A +B –A)

We know that tan(-θ) = - tan θ

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses